Applying Ho Chi Minh’s point of view on the work of cadres in the work “Modifying the working style” to this work in Vietnam today (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The work “Modifying the working style” written by President Ho Chi Minh in 1947 warned about the shortcomings, shortcomings, and mistakes of the cadres, party members, hindering the resistance war. of the nation. Over the past 70 years, the work “Modifying the way of working” is still valid because of the current news, the predictions, and predictions that President Ho Chi Minh has pointed out about the dangers to the ruling Party. His views and instructions have been inherited in building a contingent of cadres and civil servants who are both “pink” and “specialized”, in the construction of ways, manners, ethical standards, and working capacity, etc. at the same time, it has a great impact on the construction and strong development of the contingent of cadres in our country today.